Report on the 7th Hungarian Conference on Ancient Studies - Takács, Levente (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
No abstract is available for this article, published in Acta Classica Universitatis Scientiarum Debreceniensis, Issue XLIII, 2007. At the time of publication, abstracts were not required from the authors. Please consult the full text for further details.